2016
DOI: 10.3389/fpsyt.2016.00156
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Trauma and COMT Genotype Interact to Increase Hippocampal Activation in Resilient Individuals

Abstract: Both childhood trauma and a functional catechol-O-methyltransferase (COMT) genetic polymorphism have been associated with posttraumatic stress disorder (PTSD) and depression; however, it is still unclear whether the two interact and how this interaction relates to long-term risk or resilience. Imaging and genotype data were collected on 73 highly traumatized women. DNA extracted from saliva was used to determine COMT genotype (Val/Val, n = 38, Met carriers, n = 35). Functional MRI data were collected during a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 84 publications
(111 reference statements)
1
42
0
Order By: Relevance
“…Several studies have shown an association between the S allele variant of this gene and PTSD and MDD in relation to experienced stress and adversity (Karg et al, ; Xie et al, ) as well as a lower level of resilience in S allele carriers (Stein et al, ). Another promising candidate of the catecholaminergic system is COMT , whose variants also show a gene × environment interaction effect, with Met allele carriers who experienced trauma or adversity in childhood exhibiting a greater risk for the development of PTSD and depression and thus appearing to be less resilient (Valente et al, ; van Rooij et al, ). The HPA axis also appears to have an influence on resilience, particularly for the CRHR1 and FKBP5 genes, with interesting results suggesting a link between genetic variants and maltreatment during childhood and the development of PTSD and depression (Bradley et al, ; Polanczyk et al, ; Tamman et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown an association between the S allele variant of this gene and PTSD and MDD in relation to experienced stress and adversity (Karg et al, ; Xie et al, ) as well as a lower level of resilience in S allele carriers (Stein et al, ). Another promising candidate of the catecholaminergic system is COMT , whose variants also show a gene × environment interaction effect, with Met allele carriers who experienced trauma or adversity in childhood exhibiting a greater risk for the development of PTSD and depression and thus appearing to be less resilient (Valente et al, ; van Rooij et al, ). The HPA axis also appears to have an influence on resilience, particularly for the CRHR1 and FKBP5 genes, with interesting results suggesting a link between genetic variants and maltreatment during childhood and the development of PTSD and depression (Bradley et al, ; Polanczyk et al, ; Tamman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous carriers of the Met allele show lower emotional resilience against negative mood states in humans (Smolka et al, ) and exaggerated stress reactivity in mice (Papaleo et al, ). The Met allele was found to be associated with decreased inhibition‐related activation in the hippocampus, which in turn was associated with PTSD and depression symptoms in patients with childhood trauma (van Rooij et al, ). An accumulation of the Met allele was also found in individuals who developed PTSD after being exposed to urban violence (Valente et al, ).…”
Section: Candidate Genes Of the Neuroendocrine Stress Response Systemmentioning
confidence: 99%
“…Meditation has been shown to increase the thickness of the left hippocampus, the region of the brain that functions in the formation of long-term memory, emotional regulation and cognition, as well as being a critical area of the brain that plays a vital role in the resiliency to chronic stress and depressive states, possibly due to expression of hippocampal neurotrophic protein (brain-derived neurotropic factor or BDNF) [ 59 ]. Resiliency to stress, stress-related depression and post-traumatic stress are housed in the hippocampus—multiple studies have shown that increased hippocampal activation correlated negatively with post-traumatic stress disorder (PTSD) and depression symptoms, and positively with resilience [ 25 , 55 , 60 , 61 , 62 ]. PTSD patients show considerable reduction in volume of the hippocampus, decreased ventromedial PFC activity and insufficient inhibition of the amygdala, all resulting in increased fear, persistent negative emotions, impulsivity, anxiety and depressive rumination.…”
Section: Meditationmentioning
confidence: 99%
“…These neuroimaging studies have documented reduced threat-related amygdala and insula reactivity, altered reward-related responding in corticostriatal reward circuitry, and widespread changes in regional brain volumes in individuals who did not develop psychopathology. To our knowledge, only five neuroimaging studies have assessed the neural correlates of trait resilience ( Daniels et al, 2011 ; New et al, 2009 ; Reynaud et al, 2013 ; van Rooij et al, 2016 ; Waugh et al, 2008 ). Of note, these studies are all in adults.…”
Section: Introductionmentioning
confidence: 99%